Jasmonic acid and methyl dihydrojasmonate enhance saponin biosynthesis as well as expression of functional genes in adventitious roots of Panax notoginseng F.H. Chen. (25th April 2016) - Li, Jinxin; Wang, Juan; Wu, Xiaolei; Liu, Dahui; Li, Jing; Li, Jianli; Liu, Shujie; Gao, Wenyuan
Abstract: Panax notoginseng, an important herbal medicine, has wide uses for its bioactive compounds and health function. In this work, we compared the content of saponin in cultivation and adventitious root. The total content of saponins in adventitious root (8.48 mg⋅g −1 ) was found lower than in the native one (3‐year‐old) (34.34 mg⋅g −1 ). To enhance the content of bioactive compounds, we applied elicitors jasmonic acid (JA) and methyl dihydrojasmonate (MDJ) to the adventitious root culture. It was observed that the highest total content of saponins (71.94 mg⋅g −1 ) was achieved after treatment with 5 mg⋅L −1 JA, which was 2.09‐fold higher than native roots and 8.45‐fold higher than the control group. The findings from high‐performance liquid chromatography–electrospray ionization–tandem mass spectrometry analysis showed that six new compounds were present after the treatment with the elicitors. Furthermore, we found that JA and MDJ significantly upregulated the expression of the geranyl diphosphate synthase, farnesyl diphosphate synthase, squalene synthase, squalene epoxidase, dammarenediol synthase, and CYP716A47 and CYP716A53v2 (CYP450 enzyme) genes; downregulated the expression of the cycloartenol synthase gene; and increased superoxide dismutase and peroxidase activities.